ESR-SPECTRA OF V4+ IONS IN SEMICONDUCTORY V3O7 - Edwards, P; Sienko, M; Bayard, M (1977)
ESR studies on the semiconductor V3O7 reveal the existence of intrinsic paramagnetic V4+ ions. Computer simulations of spectra suggest that the unpaired electron wavefunction extends over ca. 12-14 lattice sites. This partial delocalization of the wavefunction is assumed to arise from minor crystallographic distortions at low temperatures. © 1977.